THE IMPACT OF CORPORATE GOVERNANCE MECHANISMS ON DEBT’S COST: EVIDENCE FROM CHINESE STOCK MARKETS - Waleed N. Mohammed (Scholar Express Journals, 2026)
This research examines the impact of corporate governance mechanisms on the cost of debt of listed companies in Shanghai and Shenzhen stock exchanges. Indicators assessing the quality of corporate governance as well as related qualities are used to indicate their mechanisms. Effective corporate governance, as per the principal-agent’s theory, can reduce information asymmetry and concern of shareholders. A sample of 10,630 Chinese firms for the year reference of 2021 to 2025. Further the STATA 13 was used to analyze the data. The analytical study further consists of all kinds of statistical descriptions and correlation information. It also includes an OLS Regression analysis. The key finding notes a strong negative association between corporate governance mechanisms and cost of debt suggesting that firms with able corporate leaders incur a lower cost of debt. As such, the study recommends for corporations to expand boards in other to reduce costs and enhance financial efficiency.
Keywords: Corporate Governance; Corporate Governance Quality; Debt Cost and Chinese Firms